2016
DOI: 10.1093/jisesa/iew091
|View full text |Cite
|
Sign up to set email alerts
|

Density and Egg Parasitism of Stink Bugs (Hemiptera: Pentatomidae) in Elderberry and Dispersal Into Crops

Abstract: Chinavia hilaris (Say), Euschistus servus (Say), Euschistus tristigmus (Say), and Thyanta custator custator (F.) (Hemiptera: Pentatomidae) are serious pests of crops in the southeastern United States but little is known concerning their dispersal from noncrop hosts in woodlands into crops. This 2-yr study was conducted to investigate whether elderberry [Sambucus nigra subsp. canadensis (L.) R. Bolli] in woodlands serves as a source of stink bugs dispersing into adjacent crops and to examine parasitism of C. hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…The most common parasitoid species in this study was Te. podisi, which is consistent with several previous studies (Koppel et al, 2009;Orr et al, 1986;Tillman, 2010Tillman, , 2016Tillman & Cottrell, 2016;Yeargan, 1979). An unidentified Telenomus (BIN ADI2018) was not reared out of our collected egg masses; however, it has been detected several times in sentinel egg masses of Po.…”
Section: Species-level Host-parasitoid Associationssupporting
confidence: 93%
“…The most common parasitoid species in this study was Te. podisi, which is consistent with several previous studies (Koppel et al, 2009;Orr et al, 1986;Tillman, 2010Tillman, , 2016Tillman & Cottrell, 2016;Yeargan, 1979). An unidentified Telenomus (BIN ADI2018) was not reared out of our collected egg masses; however, it has been detected several times in sentinel egg masses of Po.…”
Section: Species-level Host-parasitoid Associationssupporting
confidence: 93%
“…Based on the results of the current study and previous studies, overall percent parasitism of C. hilaris eggs ranges from 16 to 49% on various host plants (Yeargan 1979;Orr et al 1986;Jones et al 1996;Koppel et al 2009;Tillman & Cottrell 2016). In an earlier study, diversity of egg parasitoids emerging from C. hilaris was greater, and percent parasitism was higher in woodland habitats (41%) compared with those observed in crops (21%) (Tillman 2016).…”
Section: Discussionsupporting
confidence: 63%
“…Mark-recapture studies in the same woodland habitats of the current study demonstrated that elderberry (Sambucus nigra subsp. canadensis [L.] R. Bolli), a non-crop host plant of C. hilaris, was a source of this stink bug moving into cotton (Tillman & Cottrell 2016). Similarly, damage to apple by C. hilaris was greatest near woodlands (Mundinger & Chapman 1932), and infestations of this stink bug in soybean were consistently found on border rows next to woodlands (Miner 1966), suggesting that host plants in woodlands were sources of C. hilaris in apple and soybean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stink bugs movement between closely associated host plants throughout the growing season may be a response to a decrease in the availability of their current host plants (Jones and Sullivan 1982, Velasco and Walter 1992, Ehler 2000, Tillman and Cottrell 2016a. Crop-to-crop dispersal of stink bug species has been reported for many cropping systems (Tillman et al 2009, Tillman 2011, Reisig et al 2013.…”
Section: Discussionmentioning
confidence: 99%